Characterization of Phosphorus in Subtropical Coastal Sand Dune Forest Soils - Chiao-Wen Lin (Forests, 2018)
Continuous research into the availability of phosphorus (P) in forest soil is critical for the sustainable management of forest ecosystems. In this study, we used sequential chemical extraction and 31P-nuclear magnetic resonance spectroscopy (31P-NMR) to evaluate the form and distribution of inorganic P (Pi) and organic P (Po) in Casuarina forest soils of a subtropical coastal sand dune in Houlong, Taiwan. The soil samples were collected from humic (+2⁻0 cm) and mineral layers (mineral-I: 0⁻10, mineral-II: 10⁻20 cm) at two topographic locations (upland and lowland) with different elevations. Sequential chemical extraction revealed that the NaOH-Po fraction, as moderately recalcitrant P, was the dominant form in humic and mineral-I layers in both upland and lowland soils, whereas the cHCl-Pi fraction was the dominant form in the mineral-II layer. The resistant P content, including NaOH-Pi, HCl-Pi, cHCl-Pi, and cHCl-Po fractions, was higher in the upland than in the lowland. However, the labile P content, NaHCO3-Po, showed the opposite pattern. The content of resistant Pi (NaOH-Pi, HCl-Pi, and cHCl-Pi) increased significantly with depth, but that of labile Pi (resin-Pi and NaHCO3-Pi) and recalcitrant Po (NaHCO3-Po, NaOH-Po, and cHCl-Po) decreased significantly with depth at both locations. 31P-NMR spectroscopy revealed inorganic orthophosphate and monoesters-P as the major forms in this area. The proportions of Pi and Po evaluated by sequential chemical extraction and 31P-NMR spectroscopy were basically consistent. The results indicate that the soils were in weathered conditions. Furthermore, the P distribution and forms in this coastal sand dune landscape significantly differed between the upland and lowland because of the variation in elevation and eolian aggradation effects.